If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7d + -10 = 8(d + -3) Reorder the terms: -10 + 7d = 8(d + -3) Reorder the terms: -10 + 7d = 8(-3 + d) -10 + 7d = (-3 * 8 + d * 8) -10 + 7d = (-24 + 8d) Solving -10 + 7d = -24 + 8d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-8d' to each side of the equation. -10 + 7d + -8d = -24 + 8d + -8d Combine like terms: 7d + -8d = -1d -10 + -1d = -24 + 8d + -8d Combine like terms: 8d + -8d = 0 -10 + -1d = -24 + 0 -10 + -1d = -24 Add '10' to each side of the equation. -10 + 10 + -1d = -24 + 10 Combine like terms: -10 + 10 = 0 0 + -1d = -24 + 10 -1d = -24 + 10 Combine like terms: -24 + 10 = -14 -1d = -14 Divide each side by '-1'. d = 14 Simplifying d = 14
| 4(x+3)=-6(7+5x)+34x | | -8d=5-7d | | 45=-25+32x | | -b=-2b+4 | | 4(w-3)=-9w-38 | | 400-16u=15u+18+6 | | -4+3w=-7+6w | | F(5)=6 | | 10-3b+3=-1 | | 27x+8=20 | | 25n+0.08(25m)+17= | | F(5)=7 | | 62x-14-8x=16+54x-30 | | 3/4x-2/7=1/4 | | 5n-7=-2n | | X=1.1+2.7 | | A+1-5=3 | | -3(-9x+7)-5x=6(x-3)-7 | | 6c+(0.05+0.20)(6c)-10= | | X=51/4-2 | | -3x^2-12x+8=0 | | 5q+3-b+1= | | (14x+2)=57 | | 2/7(5/4)-1/7=3/4 | | x^8/2y×5y^2/x^3 | | 3y-74=31-7y | | x/3=2+x-20/5 | | 6+4x(7+8)-3= | | (12a-20b)= | | -1.51-x=4.8 | | 26=-6a-28 | | x/3=2+(x-20/5) |